Mobility-Aware Dtn Protocols for Post-Disaster Scenarios - Rosas-Olivos, E; Hidalgo-Castillo, N (Institute of Electrical and Electronics Engineers Inc., 2016)
Collecting and disseminating critical information in the direct aftermath of a disaster is very challenging: communication infrastructures are very likely to fail, and mobility becomes severely limited. Current solutions rely on traditional delay tolerant network (DTN) protocols amongst mobile devices to gather and relay vital data, but they induce an irreconcilable trade-off between delivery ratios and cost-efficiency. This paper proposes to combine protocols on every device: the mobility behavior of the device determines the routing protocol that it enforces. Simulations show that our hybrid approach minimizes message overhead and energy consumption whilst ensuring fair delivery ratios. © 2015 IEEE.